لزيادة الاستقلالية في تعلم اللغة العربية (SDL) تطبيق طريقة التعلم الذاتي - Izza Mufidah, Jiid Qoirunnisa; Huda, Hisbullah (MUHIBBUL ARABIYAH: Jurnal Pendidikan Bahasa Arab, 2025)
The self-directed learning/SDL learning model (learning from one's own experience) is a process where the initiative to learn with/or without the help of other parties is carried out by the students themselves. The essence of learning independence is that there are learning activities that are self-regulated, self-aware, and independent. The aim of this research is to determine the application of the self-directed learning method to increase independence in learning Arabic. The research method used is a quantitative experimental method. This research was conducted at MTsN 1 Sidoarjo with the research population being 338 class 7 students and the sample used was 32 class 7A students & 32 class 7B students. Data collection techniques include giving questionnaires, observations and interviews carried out using interactive communication with the Arabic language teacher. The results of the research show that the Self Directed Learning model has an effect on increasing independence in learning Arabic.